Per Flys Forestillinger: »6 uger, mennesker, virkeligheder« - Christoffersen, Erik Exe (Peripeti, 2021)
In his analysis of Danish film director Per Fly's tv-series "Forestillinger" ("Performances") Erik Exe Christoffersen demonstrates how the series unfolds en paratactic dramaturgy. Each episode presents a different and highly subjective perspective on the events around a production of Shakespeare's Venus and Adonis.